Mediterranean mysteries: notes on Plantago sect. Lancifolia (Plantaginaceae) - Hassemer, Gustavo (Phytotaxa, 2019)
Plantago sect. Lancifolia is a Mediterranean group of species with complicated nomenclature and taxonomy. In this work I present nomenclatural clarifications and taxonomic rectifications for P. altissima, P. lacustris, P. lanceolata subsp. cyrenaica, P. leiopetala and P. malato-belizii. Plantago maireana is proposed as a new name for P. lanceolata subsp. cyrenaica, and P. pilgeriana for P. lanceolata var. lacustris. Concerning P. malato-belizii and P. maireana, the conclusions presented here have important implications for biodiversity conservation, as these species are geographically very restricted. I also provide a revised identification key to all species in Plantago sect. Lancifolia.